Assessment of the COVID-19 pandemic progression in Ecuador through seroprevalence analysis of anti-SARS-CoV-2 IgG/IgM antibodies in blood donors - Gaviria, Aníbal; Tamayo-Trujillo, Rafael; Paz-Cruz, Elius; Cadena-Ullauri, Santiago; Guevara-Ramírez, Patricia; Ruiz-Pozo, Viviana A.; Cevallos, Francisco; Aguirre-Tello, Víctor; Risueño, Karla; Yánez, Martha Paulina; Cabrera-Andrade, Alejandro; Zambrano, Ana Karina (Frontiers in Cellular and Infection Microbiology, 2024)
Introduction Coronavirus Disease 2019 (COVID-19) is a severe respiratory illness caused by the RNA virus SARS-CoV-2. Globally, there have been over 759.4 million cases and 6.74 million deaths, while Ecuador has reported more than 1.06 million cases and 35.9 thousand deaths. To describe the COVID-19 pandemic impact and the vaccinations effectiveness in a low-income country like Ecuador, we aim to assess the seroprevalence of IgG and IgM antibodies against SARS-CoV-2 in a sample from healthy blood donors at the Cruz Roja Ecuatoriana. Methods The present seroprevalence study used a lateral flow immunoassay (LFIA) to detect anti-SARS-CoV-2 IgG and IgM antibodies in months with the highest confirmed case rates (May 2020; January, April 2021; January, February, June, July 2022) and months with the highest vaccination rates (May, June, July, August, December 2021) in Quito, Ecuador. The IgG and IgM seroprevalence were also assessed based on sex, age range, blood type and RhD antigen type. The sample size was 8,159, and sampling was performed based on the availability of each blood type. Results The results showed an overall IgG and IgM seroprevalence of 47.76% and 3.44%, respectively. There were no differences in IgG and IgM seroprevalences between blood groups and sex, whereas statistical differences were found based on months, age range groups, and RhD antigen type. For instance, the highest IgG seroprevalence was observed in February 2022 and within the 17-26 years age range group, while the highest IgM seroprevalence was in April 2021 and within the 47-56 years age range group. Lastly, only IgG seroprevalence was higher in RhD+ individuals while IgM seroprevalence was similar across RhD types. Discussion This project contributes to limited data on IgG and IgM antibodies against SARS-CoV-2 in Ecuador. It suggests that herd immunity may have been achieved in the last evaluated months, and highlights a potential link between the RhD antigen type and COVID-19 susceptibility. These findings have implications for public health strategies and vaccine distribution not only in Ecuador but also in regions with similar characteristics.